Meti na koš z vidika metode "Quiet eye" - Podmenik, Nadja (Šport (Ljubljana), 2013)
Joan Vickers designed the decision-making training, part of which is also the Quiet Eye (QE) method. This method is defined as the final fixation of the eye on a location that is within 3° of visual angle for a minimum of 100 ms. Special goggles are used to measure objectively the gaze. In basketball this method is very useful in shooting at the basket. General findings show that successful shots are characterised by a faster beginning of the QE and longer duration of the QE. It was established that the location of the target was not that important as the focus on the same point throughout the shooting. When the QE is used depends on the shooting technique. Research has shown some differences in the use of QE between the high and low techniques as the optimal functioning of the QE at the time of shooting differs in terms of time. The method is also considered to have a psychological effect as it helps us alleviate nervousness, better perform the task and reduce the number of injuries.
Keywords: basketball; focusing of attention; košarka; met na koš; mirno oko; pozornost; Quiet Eye; shot at the basket; sport; šport; usmerjanje pozornost